Does credit growth in the EMU banking sector follow its capital adequacy? - Draško Veselinovič; Janez Fabijan; Jaka Vadnjal (Journal of Central Banking Theory and Practice, 2023)
We put our hypothesis very straightforward, considering the euro area and the whole European Economic and Monetary Union (EMU) banking sector. The paper's central hypothesis that capital adequacy of the EMU banking sector influenced credit growth and activities in the nonfinancial sector was confirmed; however, not entirely in all respects expected. We proved that, in general, there was a dependency between banks' capital adequacy and loan growth in the euro area for the observed period Q1 1999 until Q1 2022; yet the correlation coefficient of 0.48 shows a middle positive relationship of variables. At the same time, more than 23% of loans' variability might be explained by variability in capital adequacy. All significance tests proved our results valid. Nevertheless, we saw two very different and slightly controversial dynamics in loan growth and capital ratio during the observed period. Therefore, we were forced to separately continue with an analysis for both time frames: the period before the big financial and economic crisis (Q1 1999 - Q4 2008) and the period starting with the big financial and economic crisis (Q1 2009 - Q12022). The linear regression in the pre-crisis period was almost flat. In contrast, a simple linear regression during the crisis showed a relatively high negative correlation at around -0.6. Therefore, the sub-hypothesis that higher capital adequacy resulted in negative credit growth was supported for the crisis period. We believe that this paper offers the main originality and scientific contribution for this particular finding within the data time series deployment.
Keywords: G21; 330; Banking Sector; credit activity growth; capital adequacy; financial crisis; non-performing loans; linear regression; EMU